Gastrointestinal Endoparasites Diversity of Macaca fascicularis in Goa Monyet Tenau Garden, Kupang - I Gusti Komang Oka Wirawan; Damai Kusumaningrum; Aven Bernard Oematan (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2015)
Goa Monyet Tenau Garden is one of the tourist parks located in Kupang East Nusa Tenggara Province. The population of long-tailed macaque (Macaca fascicularis) is about 142 in the region, while outside the region is 162. This study was aimed to determine the types of gastrointestinal endoparasites that infect monkeys which live inside and outside the region, and to study if there is a relationship between different regions with percentageof gastrointestinal endoparasites that infect monkeys as well. Specific target was to obtain data on the diversity of endoparasites in the tourist park. Macaca fascicularis fecal sampling was done randomly from inside and outside the region. Thirty fecal samples were taken which composed of 15 samples from the region and 15 samples from outside the region. The weight of each fecal sample is ± 10 gr. Each fecal sample was inserted into the pot(capacity ± 25 ml) and labeled by the place, date and month of collection. The samples were given 10% formalin as a preservative. Examinations were conducted at the Animal Health Laboratory Politani Kupang, using 2 methods : Centrifuge and Sedimentation method. Diversity and percentage of worm infection in monkeys between different regions were analyzed descriptively. The results showed that the types of endoparasitesinfecting monkeys inside and outside of the region were the same (Eimeria sp., Ancylostoma sp., and Strongyloides sp.). This was caused by the interaction of the use of the same region. Percentage average of endoparasitic infection that infects monkeys in the region was higher than that of outside the region (In the region: Eimeria sp./ 86.7%, Ancylostoma sp./ 73.3% and Strongyloides sp./66.7%, outside the region: Eimeriasp./ 80%, Ancylostoma sp./60%, Strongyloides sp./46.7%. The difference percentages of infection were influenced by several factors, such as vegetation, water sources, sanitation, season, temperature and population.